الآثار السلبية لاستخدام الهواتف المحمولة الذکية على العلاقات الاجتماعية والدينية (دراسة ميدانية) - نسرين محمد صادق أبو النور (Maǧallaẗ Kulliyyaẗ Al-ādāb Ǧāmiʿaẗ Būrsaʿīd, 2022)
تعتبر الهواتف الذکية احد وسائل الاتصال الاجتماعي واکثر انتشارا وشيوعا خلال العقود الأخيرة. هذه الوسائل لها مميزات وأهمية اجتماعية منها:عمليات الاتصال بين أفراد المجتمع، والمجال الديني بجانب دورها في المجال الاقتصادي (البيع -الشراء-الاعلان والصفقات التجارية)، وکذلک في مجال التعليم والصحة (التوعية- والارشادات للنواحي الاجتماعية والدينية)، وغيرها من المجالات الأخرى. وعلي الرغم من هذه الجوانب الإيجابية إلا انها لا تخلو من المشکلات والاثار السلبية کالتالي: فهي تسهم بدور کبير في تحويل العلاقات الاجتماعية من علاقات عميقة اولية الي علاقات سطحية ثانوية، ولاشک أن ذلک يهدد کيان الأسرة وتماسکها وبالتالي المجتمع ککل، بجانب الدخول إلى مواقع إباحية وغير أخلاقية مما يؤدي إلي الفقدان التدريجي للقيم التقليدية والتقاليد القديمة وتدمير القيم والأخلاق والبعد عن الجانب الديني والروحاني والإيماني.  قد تتسبب في خطورة فقدان الهوية خاصاً بين الشباب وتکوين بعض الاتجاهات والأفکار المعادية للوطن أو المنحرفة أخلاقيا" نتيجة بعض التأثيرات الخارجية السلبية والتقليد الأعمى للغرب في بعض عاداتهم وسلوکهم المختلف عن عادات المجتمعات العربية عن طريق سهوله استخدام بعض البرامج أو المواقع علي الهواتف الذکية. ومن ثم جاءت الدراسة الراهنة لتکشف عن نمط هذه الاثار السلبية وأنواعها ومدي انعکاسها على أفراد المجتمع. ومن أجل تحقيق هذه الأهداف طبقت الدراسة الراهنة على عينة عشوائية قوامها 205 مفرده من الطلاب والعاملين بجامعة المنصورة. وقد روعي في اختيار العينة أن تکون ممثله للفئات والعاملين بالجامعة. وهذا وقد استخدمت الدراسة المنهج الوصفي في تحليل المادة الميدانية کما استعانت باداه الاستبيان في جمع البيانات والمعلومات. وقد توصلت الدراسة إلى العديد من النتائج، لعل أبرزها أن: الهواتف الذکية تلعب أدوارًا مهمة وفعالة في حياة الأفراد في جميع المجالات المختلفة. بعضها سلبي ، خاصه" ما  يصاحب الاستخدام المفرط للهواتف الذکية مما يؤثر بالسوء علي التمسک والالتزام بالقيم والاتجاهات الدينية والاجتماعية.  ومنها الايجابي، مثل تفهم وتقدير أهميه بعض البرامج التطبيقية. علي سبيل المثال في المجال الصحي مثل )موقع صحه مصر) لتوعيه الافراد بفيروس الکورونا، کذلک في المجال التعليمي، تهدف برامج مثل (Zoom and Team) إلى خدمة عملية التعلم عن بعد، بالإضافة إلى التطبيقات الأخرى في جميع نواحي الحياة. Abstract Smartphones are considered one of the most popular means of social communication in recent decades. These means have advantages and social significance, including: the communication processes between members of society and the religious sphere in addition to their role in the economic field (selling - buying - advertising and commercial deals) as well as in the field of education and health (awareness - and guidance for social and religious aspects) and other  areas. Despite these positive aspects, it is not without problems and negative effects. For instance, it contributes to a major role in transforming social relations from deep primary relationships to secondary superficial relationships, and there is no doubt that this threatens the entity of the family and its solidity and accordingly, society as a whole.  Besides, there is the danger of entering pornographic and immoral sites, which leads to the gradual loss of traditional values and the destruction of morals, as well as , the  distancing  from the religious, spiritual and faith side. It may cause the risk of losing identity, especially among young people, and the formation of some anti-homeland or morally deviant trends and ideas as a result of some negative external influences and blind imitation of the West in some of their habits and behaviors that differ from the customs of Arab societies through the ease of using some programs or websites on smart phones. The current study came to reveal the pattern of these negative effects, their types and the extent of their impact on members of society. In order to achieve these goals, the current study was applied to a random sample of 205 students and workers at Mansoura University. It was taken into account in choosing the sample to be representative of the groups and workers at the university. The study used the descriptive approach in analyzing the field material, as well as the questionnaire tool used to collect data and information. The study reached many results, perhaps the most prominent of which is: Smartphones play important and effective roles in the lives of individuals in all different areas? Some of them are negative, especially that accompanies the excessive use of smartphones, which affects adherence to religious and social values ​​and trends. Others are positive, such as the understanding and appreciation of the importance of some applied programs. For example, in the health field websites like (Egypt Health) website  that strives to educate individuals about Corona virus, and in the educational field,   programs like (Zoom and Team) aim at aiding distance learning  process , that in addition to numerous applications that serve in all aspects of life.